HAMBATAN UNITED NATIONS INTERNATIONAL CHILDREN’S EMERGENCY FUND (UNICEF) DALAM MENANGANI ANAK-ANAK KORBAN KONFLIK DI PALESTINA 2022-2024 - Mandar, Arsyi Fitriana; Saeri, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The ongoing conflict in Palestine has had a devastating impact, especially on children who are the main victims of violence and instability. UNICEF, as an international organization responsible for the protection of children's rights around the world, including in Palestine, faces various challenges in carrying out its mission. This study aims to analyze the obstacles faced by UNICEF in dealing with children affected by conflict in Palestine during the period 2022-2024. The research method used is qualitative with a case study approach, where data is collected through literature review, official reports from UNICEF and related international organizations, and interviews with experts and humanitarian practitioners. The research focused on two main aspects: political and security conditions affecting UNICEF's operations, and resource and logistical limitations impacting program effectiveness. The research revealed that the unstable and frequently changing political situation is a major obstacle for UNICEF in implementing its programs. Tensions between political groups and restricted access to isolated areas hamper the distribution of humanitarian aid and health services. Aid programs designed to meet children's basic needs are often hampered by inadequate infrastructure and restricted movement. This study concludes that to improve the effectiveness of UNICEF's work in Palestine, a more inclusive policy and an adaptive approach to the dynamics on the ground are needed. Keywords: UNICEF, children affected by conflict, Palestine, barriers, humanitarian assistance.